Field evaluation of effectiveness of the BG-Sentinel, a new trap for capturing adult Aedes aegypti (Diptera: Culicidae) - Rafael Maciel-de-Freitas; Álvaro Eduardo Eiras; Ricardo Lourenço-de-Oliveira (Memorias do Instituto Oswaldo Cruz, 2006)
In recent years, the development of new tools to gather field information about vector ecological parameters has increased. This report evaluated the BG-Sentinel Trap (BGS-Trap), a promising new attempt to improve collection of the dengue vector, Aedes aegypti. The efficacy of the BGS-Trap was compared with the CDC backpack aspirator, one of the commonest used methods for capturing adult mosquitoes. BGS-Traps captured significantly more Ae. aegypti males (chi2 = 21.774, df = 1, P < 0.05) and females (chi2 = 56.007, df = 1, P < 0.05) than CDC aspirator during all days of field collection. However, CDC aspirator was significantly more efficient to capture Culex quinquefasciatus males (chi2 = 5.681, df = 1, P < 0.05) and females (chi2 = 6.553, df = 1, P < 0.05). BGS-Traps captured host-seeking females (varying between 68.75 to 89.8%) in detriment of females in other behavioral and physiological stages. BGS-Traps proved to be efficient and can be used for monitoring adult mosquito populations.